2016
DOI: 10.1177/0003319716633339
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Levels of Inflammatory Biomarkers in Peripheral Arterial Disease

Abstract: Previous research analyzed the level of plasma inflammatory markers in patients with coronary disease, but very few studies have evaluated these markers in patients with peripheral arterial disease (PAD). The objective of this study was to investigate the plasma levels of inflammatory markers in patients with PAD and in healthy controls. The following plasma levels of biomarkers were measured in 80 patients with PAD (mean age 68 ± 5 years) and in 72 healthy participants (mean age 67 ± 6 years): interleukin 6 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
48
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 48 publications
(54 reference statements)
4
48
0
1
Order By: Relevance
“…Interleukin-6 blood levels correlate with dysfunction of the endothelial cells, arterial stiffness, and predict risk of vascular events [17,18]. Decreasing the IL-6 level in patients with PAD seems to be a desirable effect, preventing progression of the disease [19]. Previously, we found that sulodexide also inhibits IL-6 release from human venous endothelial cells [9].…”
Section: Discussionmentioning
confidence: 96%
“…Interleukin-6 blood levels correlate with dysfunction of the endothelial cells, arterial stiffness, and predict risk of vascular events [17,18]. Decreasing the IL-6 level in patients with PAD seems to be a desirable effect, preventing progression of the disease [19]. Previously, we found that sulodexide also inhibits IL-6 release from human venous endothelial cells [9].…”
Section: Discussionmentioning
confidence: 96%
“…Several potential inflammatory biomarkers for the prediction of atherosclerosis have been proposed including CRP, IL-6, TNF-α, SELL, SELP, VCAM-1, ICAM-1 [39][40][41]. CRP is the most promising inflammatory biomarker predicting future cardiovascular events [42].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…1 They reported that higher plasma levels of inflammatory biomarkers were related to the development of peripheral arterial disease (PAD). 1 The cause of PAD is usually atherosclerosis.…”
mentioning
confidence: 99%
“…1 Perhaps, some of the basic and cheaper methods like C-reactive protein, neutrophil to lymphocyte ratio, and so on, could be analyzed 4 ; however, this comprehensive profile is better.…”
mentioning
confidence: 99%